COLLABORATIVE CAPABILITY AND RESPONSIBLE INNOVATION IN MSMES: BUILDING RESILIENCE THROUGH STAKEHOLDER ENGAGEMENT - Anggun Yolistina; Vip Paramarta (Journal of Jabar Economic Society Networking Forum, 2024)
This conceptual paper develops an integrative framework for collaborative capability and responsible innovation in micro, small, and medium enterprises (MSMEs). Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial-ecosystem literature, it explains how stakeholder engagement, collaborative learning, innovation governance, resource discipline, and organizational resilience can be organized into practical managerial routines. The manuscript does not claim primary survey, interview, experimental, or statistical data. It proposes a staged cycle of diagnosis, capability configuration, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention. The framework emphasizes proportionate implementation and identifies implications for owner-managers, ecosystem institutions, and future empirical research.